Integrating AI tools in EFL writing - Syafruddin, Yuliana Angreini (Pioneer: Journal of Language and Literature, 2025)
AI-assisted language learning tools such as Grammarly and ChatGPT are increasingly used in English as a Foreign Language (EFL) writing classrooms to support linguistic accuracy and drafting efficiency. However, their role in fostering critical thinking and cultural awareness remains insufficiently explored. This qualitative study investigates how undergraduate English majors at Syiah Kuala University, Indonesia, integrate Grammarly and ChatGPT into their academic writing and how cultural bias in AI-generated suggestions is recognized and addressed. Data were collected from AI-mediated students’ writing samples and semi-structured interviews and analyzed using perspectives from second language acquisition and cross-cultural communication. The findings reveal that while AI tools contribute to improved grammatical precision and lexical accuracy, they frequently generalize or flatten culturally embedded meanings, resulting in texts that are linguistically polished but culturally superficial when adopted uncritically. The study further shows that explicit pedagogical interventions, including guided reflection and critical prompts, enable students to evaluate AI feedback more critically and reinsert local cultural perspectives into their writing. These findings highlight the essential role of educators in mediating AI use and suggest that effective integration of AI in EFL writing requires balancing linguistic accuracy with the development of critical thinking and cultural literacy.